Personalidad y comunicación no verbal: acceso al argumento inconsciente por medio de los impulsores psicológicos - Maurial Chávez, lván (2011)
The present article is based on the personality evaluation from NeoAdlerian perspective (Frankl, Wexberg Titze, Berne). 1 will start presuming that human beings reveal their unconscious life plan or "argument" through their way of talking and certain non-verbal response habits which we call: "psychological driving" of small argument. The non-verbal behavior interpretation needs theoretical reference added by the author for a better underst andin g. Without talking in the name of Eric Berne's analytic theory and with the Neo Adlerian approach, the author reflects on sorne concepts related to the unconscious subject, the personality structure, the concept of finality in phycology and the counter-argument as the argument sophistication subject s: reformulating since a bio cultural approach whichthe human being interprets as a construction of double normativity.